Q-switched erbium-doped fiber laser using thulium fiber saturable absorber - Rosdin, Raja Zaimas Rosdin Raja; Arof, Hamzah; Apsari, Retna; Harun, Sulaiman Wadi (Old City Publishing, 2018)
We demonstrated a passive Q-switched Erbium-doped fiber laser (EDFL) based on Thulium fiber saturable absorber (SA). The EDFL generates a Q-switching pulse operating at 1564 nm as the pump power is increased above the threshold pump power of 66 mW. The Q-switching operation is maintained before disappearance when the pump power is above 104 mW. This is due to the fact that the thulium fiber could not fully recover in time after a pulse and less gain populations is excited before the next pulsing. With the SA, the laser produces a stable pulse train with repetition rate ranging from 2.18 to 3.16 kHz and the pulse width reduces from 127.4 to 75.4 µs while varying the pump power from 66 mW to 104 mW. The maximum pulse energy of 8.2 nJ is obtained at a pump power of 104 mW. The advantages of the fiber based saturable-absorbers are their ability to hold enormous gain excited in the gain fiber from lasing and their high damage threshold for high-power Q-switched pulses.